A Parametric Study on the Flexural Strengthening of Reinforced Concrete Beams with Near Surface Mounted FRP Bars - Minu Panahi; Mohsen Izadinia (Salehan Institute of Higher Education, 2018)
FRP rods as lightweight materials with extraordinary properties of high strength to weight ratio, corrosion resistance, potentially high overall durability, tailor ability and high specific attributes are one of the most favorable materials to strengthen existing reinforced structures. The present study aimed to identify the behavior of reinforced concrete flexural beams strengthened with fiber reinforced polymer (FRP) rods through near surface mounted method (NSM). The results of the current study were based on nonlinear finite element software ABAQUS which can accurately simulate the experimental investigations on flexural behavior of reinforced concrete beams strengthened with NSM FRP rods. Validation of the proposed model was confirmed first by making a comparison with the experimental study presented in the literature. A parametric analysis was conducted on validated specimens to investigate the effect of FRP rod diameters, rod arrangements, FRP materials, as well as rods groove intervals on flexural behavior of strengthened reinforced beams. The numerical results of mid-span bending moment deflection, ultimate bending moment, failure deflection and ductility index were reported. For the sake of simplicity to be used by engineers, the results of the current study were drawn in the form of design charts and tables.